Single‐cell transcriptomic atlas of distinct early immune responses induced by SARS‐CoV‐2 Proto or its variants in rhesus monkey - Yun Yang; Tingfu Du; Wenhai Yu; Yanan Zhou; Chengyun Yang; Dexuan Kuang; Junbin Wang; Cong Tang; Haixuan Wang; Yuan Zhao; Hao Yang; Qing Huang; et al. (MedComm, 2023)
Abstract Immune responses induced by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection play a critical role in the pathogenesis and outcome of coronavirus disease 2019 (COVID‐19). However, the dynamic profile of immune responses postinfection by SARS‐CoV‐2 variants of concern (VOC) is not fully understood. In this study, peripheral blood mononuclear cells single‐cell sequencing was performed to determine dynamic profiles of immune response to Prototype, Alpha, Beta, and Delta in a rhesus monkey model. Overall, all strains induced dramatic changes in both cellular subpopulations and gene expression levels at 1 day postinfection (dpi), which associated function including adaptive immune response, innate immunity, and IFN response. COVID‐19‐related genes revealed different gene profiles at 1 dpi among the four SARS‐CoV‐2 strains, including genes reported in COVID‐19 patients with increased risk of autoimmune disease and rheumatic diseases. Delta‐infected animal showed inhibition of translation pathway. B cells, T cells, and monocytes showed much commonality rather than specificity among the four strains. Monocytes were the major responders to SARS‐CoV‐2 infection, and the response lasted longer in Alpha than the other strains. Thus, this study reveals the early immune responses induced by SARS‐CoV‐2 Proto or its variants in nonhuman primates, which is important information for controlling rapidly evolving viruses.